Results of the research of the basic model of multifunctional tillage unit - S. L. Demshin; D. A. Cheremisinov; V. P. Ostal’tsev; V. V. Ilyichev (Аграрная наука Евро-Северо-Востока, 2019)
The analysis of equipment for basic boardless plowing and surface tillage revealed the absence in the market of agricultural machinery of multifunctional units capable of reliable and efficient performing both types of tillage by means of one machine. The constructive-technological scheme is offered and the basic model of the unit with replaceable working bodies is developed: flat hoes for performance of the basic processing of soil at 14-25 сm with the creation of a mulch layer and cultivator hoes for carrying out the surface and shallow tillage at 5-14 cm. To assess the effectiveness of the basic model of the unit in 2018 in field conditions a research was carried out, during which the main agrotechnical indicators of the quality of soil treatment were determined. Studies have shown that the degree of crumbling of the soil at the basic boardless plowing of sod-podzolic medium loamy soil at a speed of more than 6.5 km/h exceeded 80 %.  For shallow tillage to a depth of 12 cm  in the range  of operating speeds above 7.0 km/h the amount of a soil fraction up to 25 mm was not less than 70 %. The unit stably sustains the working coverage width and the installation depth of tillage. The variant of the unit with a set of working bodies for the basic boardless plowing in the entire range of operating speeds provides an average tillage depth of 19.5-21.0 cm at an installation depth of 20 cm, with working bodies for shallow tillage - of 11.5-12.0 cm at an installation depth of 12 cm. The height of roughness of the field surface after the basic boardless plowing was 20.7-23.0 mm, for shallow tillage – 12.5-17.0 mm. The results of the research showed that the basic model of the multifunctional unit can perform the basic boardless plowing and shallow tillage in compliance with the basic agrotechnical requirements without the use of replaceable adapters for additional tillage of the top layer of soil. The use of additional working bodies will make it possible to form more highly specialized versions of the machine based on the basic model of the unit.